2011
DOI: 10.1258/ijsa.2009.009463
|View full text |Cite
|
Sign up to set email alerts
|

Post-exposure prophylaxis following sexual exposure to HIV: a seven-year retrospective analysis in a regional centre

Abstract: An audit of 72 patients presenting for post-exposure prophylaxis following sexual exposure (PEPSE) to HIV (68 genitourinary medicine and 4 accident & emergency) was conducted from 2003 to 2009. The principal indications for PEPSE included 27 (38%) unprotected intercourse (15/27 vaginal and 12/27 anal) with a known HIV-positive partner, 20 (28%) unprotected receptive anal sex with male partner of unknown status, 17 (24%) following sexual assault and three (4%) unprotected sex with a partner from an endemic coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
2
14
0
2
Order By: Relevance
“…In surveys conducted among attendees at the Seattle Gay Pride parade (2009–2012) only 26% of attendees were aware of nPEP [unpublished data, Elizabeth Barash]. The majority of studies, with a few exceptions [6], [28], report low demand for nPEP [13], [29][31]. In order to access and benefit from nPEP, individuals must overcome many barriers: 1) recognize an exposure to HIV; 2) be aware of nPEP and where to obtain it; 3) report for care within 72 hours of exposure; 4) have the means to pay for nPEP if they are un- or under-insured and cannot access assistance programs; and 5) preferably know or determine the HIV status of her/his contact.…”
Section: Discussionmentioning
confidence: 99%
“…In surveys conducted among attendees at the Seattle Gay Pride parade (2009–2012) only 26% of attendees were aware of nPEP [unpublished data, Elizabeth Barash]. The majority of studies, with a few exceptions [6], [28], report low demand for nPEP [13], [29][31]. In order to access and benefit from nPEP, individuals must overcome many barriers: 1) recognize an exposure to HIV; 2) be aware of nPEP and where to obtain it; 3) report for care within 72 hours of exposure; 4) have the means to pay for nPEP if they are un- or under-insured and cannot access assistance programs; and 5) preferably know or determine the HIV status of her/his contact.…”
Section: Discussionmentioning
confidence: 99%
“…This compares favourably with the Victorian nPEP program which reported that 34% of nPEP clients had been tested at three month follow-up [13]. Hospitals in the UK [14] and France [15] have also reported low follow-up testing of nPEP clients after three months (35% and 29% respectively). Studies examining testing rates over time further highlight the challenge of improving post-nPEP testing.…”
Section: Discussionmentioning
confidence: 68%
“…Of these women who received nPEP, only 41% returned for follow-up at 2, 4, 12, and 24 weeks, of which 60% reported taking at least 21 days of the prescribed course of therapy [23]. Other retrospective studies involving nPEP following high-risk exposures including SA from other countries have reported similar completion rates between 60% and 64% [24,25].…”
Section: Key Questionmentioning
confidence: 96%